The Impact of Social Media Influencer Credibility on Consumer Purchase Decisions: A Study on Originote Skincare - Titi Halimah; Anas Hidayat (Universitas Negeri Semarang, 2025)
Social media platforms’ emergence and rapid growth have significantly transformed how consumers behave, especially within the beauty industry. In this realm, influencer marketing has evolved into a crucial strategy that brands increasingly rely on to connect with their audience. This research focuses on influencer reviews' impact on consumers' purchasing choices regarding The Originote skincare products. It considers various moderating factors, including convenience, interactivity, and the source's credibility, to understand this phenomenon comprehensively. This research delves into the intricate dynamics of consumer attitudes by examining various theoretical frameworks, including the Source Credibility Theory and the Theory of Planned Behavior. It specifically focuses on the pivotal roles that trustworthiness, expertise, and attractiveness play in shaping how consumers perceive social media influencers and the products they promote. Through this exploration, the study aims to uncover the underlying mechanisms that drive consumer behavior in the context of influencer marketing. A quantitative approach was utilized in this study, engaging 301 respondents who took part in a meticulously structured online survey. The analysis of the data gathered from a varied sample of consumers was conducted using Structural Equation Modeling (SEM) in conjunction with Partial Least Squares (PLS) methodology. The study results indicate that convenience and interactivity are crucial in shaping consumer attitudes toward influencers. The findings presented here offer significant insights for marketers looking to utilize influencers as effective advocates in promoting affordable and accessible skincare products such as The Originote.